(untitled) (Research, Society and Development, 2021)
Introduction: Femoral fractures in elderly women usually are associated to high morbid-mortability. The purpose of this study was to identify factors associated to femoral fractures in the elderly women (≥ 60 years). Methods: It was a cohort study with elderly women who underwent surgical procedures between 2000 and 2015. We used a socio-demographic/clinical data collection instrument and the European Vertebral Osteoporosis Study Group (EVOS). Data were analyzed by descriptive statistics, Student t-test and Chi-square test with a significance level of p <0.05. The study was approved by the institution’s Ethics Committee for Research with Human Subjects. Results: Eighteen women were included in analysis. The mean(±SEM) age at fracture time was 74.43±2.35 years. median[95%CI] age of menopause of 48.00[41.48–51.74] years, mean(±SEM) menopause time of 33.65±3.43 Fracture due to fall (77.8%). Most of of the interviewed women did not use of medication for treatment of osteoporosis. Conclusion: These results suggest the vulnerability of the participants to new fractures, indicating the need for greater attention to the health-illness-care process.